A Growth Model For International Education In Developing Countries - Nguyen, Hoang T.; Ma′ruf, Ma′ruf; Stoffers, Jol (Jurnal Administrasi Bisnis, 2015)
This papers objective is to build a collaboration framework to marshal the international cooperation among universities, not only within the same region in developing countries but also with developed countries. The research is based on selected case studies, which consists of top universities in Vietnam, Indonesia, Australia, the Netherlands, and the worldwide universities network. The suggested framework involves two core activities, which are teaching and learning, and research. These are influenced by required resources, policy, and accreditation. The key for successful collaboration lies in the relations between these elements; therefore, the collaboration will not necessarily follow a continuum. Keywords: collaboration in higher education, university